Acclimation of rice photosynthesis to irradiance under field conditions - Murchie, Erik H.; Hubbart, Stella; Chen, Yizhu; Peng, Shaobing; Horton, Peter (Oxford University Press, 2002)
Acclimation to irradiance was measured in terms of light-saturated photosynthetic carbon assimilation rates (Pmax), Rubisco, and pigment content in mature field-grown rice (Oryza sativa) plants in tropical conditions. Measurements were made at different positions within the canopy alongside irradiance and daylight spectra. These data were compared with a second experiment in which acclimation to irradiance was assessed in uppermost leaves within whole-plant shading regimes (10% low light [LL], 40% medium light [ML], and 100% high light [HL] of full natural sunlight). Two varieties, japonica (tropical; new plant type [NPT]) and indica (IR72) were compared. Values for Rubisco amount, chlorophyll a/b, and Pmax all declined from the top to the base of the canopy. In the artificial shading experiment, acclimation of Pmax (measured at 350 μL L−1 CO2) occurred between LL and ML for IR72 with no difference observed between ML and HL. The Rubisco amount increased between ML and HL in IR72. A different pattern was seen for NPT with higher Pmax (measured at 350 μL L−1CO2) at LL than IR72 and some acclimation of this parameter between ML and HL. Rubisco levels were higher in NPT than IR72 contrasting with Pmax. Comparison of data from both experiments suggests a leaf aging effect between the uppermost two leaf positions, which was not a result of irradiance acclimation. Results are discussed in terms of: (a) acclimation of photosynthesis and radiation use efficiency at high irradiance in rice, and (b) factors controlling photosynthetic rates of leaves within the canopy.